Mango value chain in Trinidad and Tobago,Guyana and St. Lucia: Measuring and reducing post-harvest losses - Mohammed, M; Mpagalile, J; Lopez , V; Craig, k (Journal of Postharvest Technology, 2018)
Measurements of post-harvest losses of fresh mango fruits and processed mango products were conducted after screening the value chains harvest losses of fresh mango fruits and processed mango products were conducted after screening the value chains harvest losses of fresh mango fruits and processed mango products were conducted after screening the value chains in Trinidad and Tobago, Guyana and St. Lucia. Based on the critical loss points (CLPs) where losses had the highest magnitude, the highest in Trinidad and Tobago, Guyana and St. Lucia. Based on the critical loss points (CLPs) where losses had the highest magni in Trinidad and Tobago, Guyana and St. Lucia. Based on the critical loss points (CLPs) where losses had the highest magni impact on food security, and the highest effect on the economic result of the food supply chain (FSC), appropriate solutions were impact on food security, and the highest effect on the economic result of the food supply chain (FSC), appropriate solutions impact on food security, and the highest effect on the economic result of the food supply chain (FSC), appropriate solutions recommended to optimize the system to reduce losses. The CLPs for fresh table ripe mangoes were similar in Trinidad and Tobago and recommended to optimize the system to reduce losses. The CLPs for fresh table ripe mangoes were similar in T recommended to optimize the system to reduce losses. The CLPs for fresh table ripe mangoes were similar in T Guyana, with at harvest as CLP#1 and retail markets as CLP#4. For St. Lucia the CLPs identified for fresh mango fruits wholesaled to the Guyana, with at harvest as CLP#1 and retail markets as CLP#4. For St. Lucia the CLPs identified for fresh mango fruits wholes Guyana, with at harvest as CLP#1 and retail markets as CLP#4. For St. Lucia the CLPs identified for fresh mango fruits wholes